Nutritional, Textural, and Sensory Attributes of Protein Bars Formulated with Mycoproteins - Xiao-Yan You; Yue Ding; Qing-Yun Bu; Qin-Hong Wang; Guo-Ping Zhao (Foods, 2024)
Research accumulated over the past decades has shown that mycoprotein could serve as a healthy and safe alternative protein source, offering a viable substitute for animal- and plant-derived proteins. This study evaluated the impact of substituting whey protein with fungal-derived mycoprotein at different levels (10%, 20%, and 30%) on the quality of high-protein nutrition bars (HPNBs). It focused on nutritional content, textural changes over storage, and sensory properties. Initially, all bars displayed similar hardness, but storage time significantly affected textural properties. In the early storage period (0–5 days), hardness increased at a modest rate of 0.206 N/day to 0.403 N/day. This rate dramatically escalated from 1.13 N/day to 1.36 N/day after 5 days, indicating a substantial textural deterioration over time. Bars with lower mycoprotein levels (10%) exhibited slower hardening rates compared with those with higher substitution levels (20% and 30%), pointing to a correlation between mycoprotein content and increased bar hardness during storage. Protein digestibility was assessed through in vitro gastric and intestinal phases. Bars with no or low-to-medium levels of mycoprotein substitution (PB00, PB10, and PB20) showed significantly higher digestibility (40.3~43.8%) compared with those with the highest mycoprotein content (PB30, 32.9%). However, digestibility rates for all mycoprotein-enriched bars were lower than those observed for whey-protein-only bars (PB00, 84.5%), especially by the end of the intestinal digestion phase. The introduction of mycoprotein enriched the bars’ dietary fiber content and improved their odor, attributing a fresh mushroom-like smell. These findings suggest that modest levels of mycoprotein can enhance nutritional value and maintain sensory quality, although higher substitution levels adversely affect texture and protein digestibility. This study underscores the potential of mycoprotein as a functional ingredient in HPNBs, balancing nutritional enhancement with sensory acceptability, while also highlighting the challenges of textural deterioration and reduced protein digestibility at higher substitution levels.